The mathematical model of the task of compiling the time-table - Литвиненко, О.Є.; Краліна, Г.С.; Стьопушкіна, О.П (Proceedings of National Aviation University, 2004)
The mathematical model of the task of compiling the time-table in High-school has been carried out. It has been showed, that the task may be reduced to canonical form of extrimal combinatorial tasks with unlinear structure after identical transformations. The algorithm of the task’s decision for realizing the scheme of the directed sorting of variants is indicated.